Dynamic Marketing and Service Innovation for Service Excellence - Hariandja, Evo S.; Simatupang, Togar M.; Nasution, Reza A.; Larso, Dwi (Gadjah Mada International Journal of Business, 2014)
This study aims at creating a framework describing how the interaction capabilities between dynamic marketing and service innovation can influence service excellence. In this study market sensing, market learning, market targeting or positioning are classified as dynamic marketing capabilities (DMC), while sensing, seizing, and transformi ng are classified as service innovation capabilities (SIC). Hence, the drivers of service excellence for the framework being developed are divided into three main categories: dynamic marketing capability, service innovation capability, and their interaction. The findings of the study on three hotels, ranging from 4-star to 5-star hotels and operating in Indonesia, suggest that both capabilities and their interaction play their roles in achieving service excellence.